Comparison between a non-hydrostatic model and OpenFOAM for 2D wave-structure interactions. (1st July 2019) - Ma, Yuxiang; Yuan, Changfu; Ai, Congfang; Dong, Guohai
Abstract: This paper presents comparisons between a non-hydrostatic free surface model and OpenFOAM for predicting wave-structure interactions. The non-hydrostatic model solves the incompressible Euler equations by the use of an explicit projection method and treats free surface elevations as a single-valued function of the horizontal position. The immersed boundary method is incorporated in the model to deal with structures. Three test cases related to wave interactions with a fixed floating structure or a submerged structure are considered in the comparison. Very good agreement between the results from the two models is obtained in terms of free surface elevations and wave forces, demonstrating that the presented non-hydrostatic model is comparable to the OpenFOAM in wave-structure interactions involving single-valued free-surface flows.